On the continuous dependence of solutions to orthogonal additivity problem on given functions - Baron, Karol (Annales Mathematicae Silesianae, 2015)
We show that the solution to the orthogonal additivity problem in real inner product spaces depends continuously on the given function and provide an application of this fact.